"The Permanent Truth of Hedonist Moralities": Plato and Levinas on Pleasures. Issue 52 (3rd April 2021) - Staehler, Tanja; Kozin, Alexander
ABSTRACT: Levinas maintains that there is a lasting significance to hedonism if we consider the important role of pleasures for our embodied existence. In this essay, we go back to Plato to explore the nature of pleasure, different kinds of pleasures, and their contribution to the good life. The good life is a considerate mixture of pleasures which requires knowing, understanding and remembering. Pleasures take us to the most basic level of existence which the Presocratics can help us understand through their idea of elements. With the help of Levinas, we can expand the concept of elements to include elemental states. As a result, we see how our embodied existence opens us up to various levels of otherness.